System analysis of water resources and proposal of sustainable water resources allocation for Ba River Catchment - Tam, Vu Thanh; Hung, Do Tien; Le, Tran Thanh (Vietnam Journal of Earth Sciences, 2012)
In this paper, a system analysis methodology is tested in conjunction with the application of the Water Evaluation And Planning (WEAP) package to analyze the effectiveness of water resources allocation and sharing in the Ba River water scarce Catchment. Principal components of the catchment water resources system such as infrastructure, major water users and stakeholders, policies and plans on socio-economic development and water resources management are identified and defined by separate regions of the catchment. Three scenarios are constructed: the first scenario represents economic-socio-water resources infrastructure conditions and water resources management reality of the catchment in the period 2000-2010; the second one is an imaginary application of the currently issued multi-reservoir operation rule for the 5 largest hydropower reservoirs in the same economic-socio-water resources infrastructure conditions of the catchment for the period 2000-2010; and the third scenario simulates the water usage and sharing in accordance with the economic-social development of the catchment in the period 2011-2020 when the multi-reservoir operation rule is actually implemented and a portion of Ba River water is diverted to a neighbourhood catchment for hydropower production. The WEAP system combining embedded simulations of reservoir operation and rainfall-runoff as well as surface-ground water interaction processes is used to analyze and obtain an insight into performance of components of the water resources system in the above-mentioned three scenarios. Comparison of the three scenarios was done on the basis of meeting the water demand of major water users, groundwater and reservoir storage variation in time, which unveils inadequacies of the current reservoir operation rule. Besides, the analysis result shows that:- The water shortage often occurs in many localities of the Ba Catchment, especially in the intermediate zone, during period from January till May every year, and is attenuated from scenario Ia to Ib to II;- In the period 2011-2020 the water use demand exceeds the limit which can be affored by the catchment;- Given a flow requirement of larger than 3 m3/s and 20 m3/s is imposed right downstream of the An Khe dam and at Cung Son, respectively, the An Khe hydropower plant can only operates at 54% of its designed capacity. The higher the power generation, the less water demand coverage at the downstream localities.A set of measures are therefore proposed to ensure the minimal meet rate at 70% of monthly water demand for all major water users in the catchment for the period 2011-2020.